Limiting factors of investment activity of the sports industry on the example of international football competitions in Russia - Dougblay, A.D.; Lubyshev, E.A.; Titovsky, A.V.; Krasilnikov, A.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the limiting factors of investment activity in the organization and holding of international football competitions in Russia. Results and conclusions. The article assesses the degree of realization of the sports potential of Russia, taking into account the problems of financing priority areas in the field of physical culture and sports, using the example of major international sports projects in Russia. It is assumed that a cumulative solution to all existing financing problems is possible only on the basis of certain comprehensive actions in all relevant priority areas. Successful activity in the sports and physical culture industry entails the development of related industries, such as the construction industry, tourism. For systematic and rational investment activities in the field of physical culture and sports, it is necessary to resort to a larger-scale implementation of vertical integration mechanisms adjusted for a particular sport, when training centers are created on the basis of professional sports clubs not only in the direction of sports training (preparation of a sports reserve), but also in the direction of sports management, as well as the training of sports coaches and referees.